2016
DOI: 10.1007/s00384-016-2624-4
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic superior mesenteric vein injury: the perils of high ligation

Abstract: Iatrogenic superior mesenteric vein injury is a rare, severe, and underreported complication of both open and laparoscopic right colectomy for colonic adenocarcinoma. We identified several mechanisms of injury such as anatomic misperception, excessive traction and pulling on the venous system, extensive tumor involvement of the mesentery, and uncontrolled suturing attempts at hemostasis. We believe that increased awareness of this complication with profound understanding of vascular anatomy and the different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 4 publications
0
24
0
1
Order By: Relevance
“…Freund et al . described five cases (1.6%) of SMV injuries from a total of 304 radical right colectomies 73 . Only two of these injuries were observed during the initial surgery, and three patients required saphenous graft reconstruction, with one postoperative death 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Freund et al . described five cases (1.6%) of SMV injuries from a total of 304 radical right colectomies 73 . Only two of these injuries were observed during the initial surgery, and three patients required saphenous graft reconstruction, with one postoperative death 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Freund et al . reported a total iatrogenic superior mesenteric vein injury rate of 1.6% (5/304) when performing central ligation in right‐sided colon cancer. Bertelsen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some possible mechanisms of superior mesenteric vein injury include anatomic variations and avulsion of the middle colic vein due to excessive traction. Freund et al [29] reported a total iatrogenic superior mesenteric vein injury rate of 1.6% (5/304) when performing central ligation in right-sided colon cancer. Bertelsen et al [22] reported a higher rate of intra-operative injury to organs including injury to the superior mesenteric vein, splenic injury and injury to other segments of the colon in CME than in NCME (9.1% vs 3.6%, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Dies kann das bekannte Risiko von iatrogenen Gefäßverletzungen bei der CME bzw. ZGL reduzieren [12]. Dies wirkt sich insbesondere bei adipösen Patienten aus, bei denen es intraperitoneal regelhaft erschwert ist, die ileokolischen Gefäße in toto anzuspannen, wie es beim klassischen medial-zu-lateralen Ansatz zum Freilegen des Mesocolon ascendens im Rahmen der CME üblich ist.…”
Section: Operationstechnikunclassified